Ageing, migration and new media: The significance of transnational care. (June 2018) - Wilding, Raelene; Baldassar, Loretta
The experiences of ageing for today's older people present a striking contrast to those of the past. They are entering older age in a world that is characterised by complex mobilities and flows, in which large numbers of people are ageing in countries other than the one in which they were born and often at a distance from their closest family members. At the same time, new media are providing unprecedented opportunities to bring distant places and people together in new ways. These dramatic shifts are transforming the context within which older people provide and receive care. In this article, we argue that it has become both necessary and urgent for researchers and practitioners of ageing to reconsider their emphasis on the proximate care networks of older people, by incorporating closer attention to the increasingly global, transnational and virtual contexts within which ageing and aged care now routinely takes place.